2003
DOI: 10.1152/ajpgi.00534.2002
|View full text |Cite
|
Sign up to set email alerts
|

CaM kinase II regulation of CRHSP-28 phosphorylation in cultured mucosal T84 cells

Abstract: blewski. CaM kinase II regulation of CRHSP-28 phosphorylation in cultured mucosal T84 cells. Am J Physiol Gastrointest Liver Physiol 285: G1300-G1309, 2003. First published July 31, 2003 10.1152 10. /ajpgi.00534.2002 -regulated heat-stable protein of 28 kDa (CRHSP-28; a member of the tumor protein D52 family) is highly expressed in exocrine glands and was shown to regulate digestive enzyme secretion from pancreatic acinar cells. We found CRHSP-28 highly expressed in cultured mucosal secretory T84 cells, consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Indeed, CRHSP28 has been recently shown to be serine phosphorylated upon increasing Ca 2ϩ levels in epithelial cells. 45 Finally, it has been reported that in rat pancreatic acinar cells, CRHSP28 can bind annexin VI in a calcium-dependent way and that this molecular complex plays an important role in acinar cell membrane trafficking events that are essential for digestive enzyme secretion. 14 Our finding-that in the Thiel human myeloma cell line, TPD52 associates to annexin VI in a Ca 2ϩ -dependent manner-raises the intriguing possibility that these molecules may act in concert to regulate secretory processes also in plasma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CRHSP28 has been recently shown to be serine phosphorylated upon increasing Ca 2ϩ levels in epithelial cells. 45 Finally, it has been reported that in rat pancreatic acinar cells, CRHSP28 can bind annexin VI in a calcium-dependent way and that this molecular complex plays an important role in acinar cell membrane trafficking events that are essential for digestive enzyme secretion. 14 Our finding-that in the Thiel human myeloma cell line, TPD52 associates to annexin VI in a Ca 2ϩ -dependent manner-raises the intriguing possibility that these molecules may act in concert to regulate secretory processes also in plasma cells.…”
Section: Discussionmentioning
confidence: 99%
“…SDS-PAGE and immunoblotting were conducted as previously described (38). Anti-D52 (5 g/ml)-HA (1:1,000), -syntaxin 2-4 (1:1,000), -VAMP2 (1:2,000), and -VAMP8 (1:1,000), -syt1 (1:2,000), and -AP-3 (1:1,000) immunoreactivities were detected by using appropriate horseradish peroxidase-conjugated secondary antibodies.…”
Section: G442mentioning
confidence: 99%
“…D52 phosphorylation is Ca 2ϩ dependent and potentially mediated by the ␦6-isoform of CaM kinase II (15,38). In acinar cells, D52 phosphorylation is maximal within 2 min of secretagogue stimulation and then rapidly declines by 15 min (38 -39).…”
Section: G448mentioning
confidence: 99%
“…It also has been reported that D52 tumor proteins are involved in Ca 2ϩ signaling to regulate proliferation and Ca 2ϩ -stimulated secretory activity (37,38). Recently, it has been reported that calcium/ calmodulin-dependent protein kinase II phosphorylates a Ca 2ϩ -regulated heat-stable protein of 28 kDa (CRHSP-28; a member of the tumor protein D52 family) in cultured mucosal T84 cells (39). Thus, our finding that hD53L1, a member of the tumor protein D52 family, activates the ASK1 pathway suggests that it may play a role in the Ca 2ϩ -dependent ASK1-regulating pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that hD53L1 may require other cellular factor(s) or external stimuli to gain full activity. Calcium may also be involved in the regulation, since calcium/calmodulin-dependent protein kinase II acts on both ASK1 and D52 family (35,39). These possibilities suggest that the regulation mechanism of ASK1 by hD53L1 may be different from the mechanisms of ASK1 by Daxx and TRAF2.…”
Section: Discussionmentioning
confidence: 99%